Mapping of HIV-1C Transmission Networks Reveals Extensive Spread of Viral Lineages Across Villages in Botswana Treatment-as-Prevention Trial. (3rd June 2020) - Novitsky, Vlad; Zahralban-Steele, Melissa; Moyo, Sikhulile; Nkhisang, Tapiwa; Maruapula, Dorcas; McLane, Mary Fran; Leidner, Jean; Bennett, Kara; ,; Wirth, Kathleen E; Gaolathe, Tendani; Kadima, Etienne; et al.
Abstract: Background: Phylogenetic mapping of HIV-1 lineages circulating across defined geographical locations is promising for better understanding HIV transmission networks to design optimal prevention interventions. Methods: We obtained near full-length HIV-1 genome sequences from people living with HIV (PLWH), including participants on antiretroviral treatment in the Botswana Combination Prevention Project, conducted in 30 Botswana communities in 2013–2018. Phylogenetic relationships among viral sequences were estimated by maximum likelihood. Results: We obtained 6078 near full-length HIV-1C genome sequences from 6075 PLWH. We identified 984 phylogenetically distinct HIV-1 lineages (molecular HIV clusters) circulating in Botswana by mid-2018, with 2–27 members per cluster. Of these, dyads accounted for 62%, approximately 32% (n = 316) were found in single communities, and 68% (n = 668) were spread across multiple communities. Men in clusters were approximately 3 years older than women (median age 42 years, vs 39 years; P < .0001). In 65% of clusters, men were older than women, while in 35% of clusters women were older than men. The majority of identified viral lineages were spread across multiple communities. Conclusions: A large number of circulating phylogenetically distinct HIV-1C lineages (molecular HIV clusters) suggests highly diversified HIV transmission networks across Botswana communities by 2018. Abstract : Using designed sampling and high genotyping density, the study produced 6078 near full-length HIV-1C genome next-generation sequences and identified 984 phylogenetically distinct molecular clusters. The complex structure of the country-wide HIV-1C transmission network in Botswana was revealed, mapped, and characterized.